Good Governance in Regional Official Vehicle Management: An Islamic Education Management Perspective - Ahmad Hidir Amin; Ibnu Elmi A. S. Pelu (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the implementation of good governance principles in the management of official vehicles as part of Regional Property (BMD) and examine it from the perspective of Islamic Education Management (MPI). The study uses a qualitative approach with a case study design through in-depth interviews, document analysis, and administrative observation of the management of official vehicles in the local government environment. The results show that of the 241 active vehicles, 214 (88.8%) have a valid user decree (SK), while 27 (11.2%) have not been renewed due to job rotation dynamics. These findings indicate that administrative legality has been relatively fulfilled, but consistency in administrative accountability has not been fully achieved. The ongoing governance practices are still dominated by procedural compliance (rule-based compliance) and are not yet fully oriented towards performance-based accountability. From an MPI perspective, public asset management is not only understood as regulatory compliance, but as a practice of stewardship that demands integrity, responsibility, and public interest. This study emphasizes that strengthening regional asset governance requires the integration of digital-based administrative system reforms, bureaucratic capacity building, and the internalization of ethical-spiritual values in organizational practices. Conceptually, this study contributes to the development of an integrative approach between good governance and Islamic Education Management values in public asset governance.